Contemporary Algorithm for the Management of Hepatocellular Carcinoma in 2021: The Northwestern Approach - Swersky, Adam; Kulik, Laura; Kalyan, Aparna; Grace, Karen; Caicedo, Juan Carlos; Lewandowski, Robert J.; Salem, Riad (Seminars in Interventional Radiology, 2021)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer and a major cause of cancer-related morbidity and mortality around the world. Frequently, concurrent liver dysfunction and variations in tumor burden make it difficult to design effective and standardized treatment pathways. Contemporary treatment guidelines designed for an era of personalized medicine should consider these features in a more clinically meaningful way to improve outcomes for patients across the HCC spectrum. Given the heterogeneity of HCC, we propose a detailed clinical algorithm for selecting optimal treatment using an evidence-based and practical approach, incorporating liver function, tumor burden, the extent of disease, and ultimate treatment intent, with the goal of individualizing clinical decision making.
Keywords: radioembolization; yttrium-90; downstaging; transplantation; survival; interventional radiology